2002
DOI: 10.1001/jama.287.22.2951
|View full text |Cite
|
Sign up to set email alerts
|

Patient Complaints and Malpractice Risk

Abstract: Unsolicited patient complaints captured and recorded by a medical group are positively associated with physicians' risk management experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
326
1
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 479 publications
(345 citation statements)
references
References 26 publications
(37 reference statements)
9
326
1
4
Order By: Relevance
“…Similarly, among the reasons that claimants interviewed by Hickson and colleagues [18] gave as motivating their lawsuits were the belief that ''the courtroom was the only forum in which they could find out what happened from the physicians who provided care'' (20%), the belief ''that physicians had failed to be completely honest with them about what happened, allowed them to believe things that were not true, or intentionally misled them'' (24%), and a desire to ''deter subsequent malpractice by the physician and/or to seek revenge'' (19%) [18]. Other studies have similarly found failure to provide explanations and poor communication generally are associated with litigation [1,19,21,34,35,48].…”
Section: Apologies and Patientsmentioning
confidence: 99%
“…Similarly, among the reasons that claimants interviewed by Hickson and colleagues [18] gave as motivating their lawsuits were the belief that ''the courtroom was the only forum in which they could find out what happened from the physicians who provided care'' (20%), the belief ''that physicians had failed to be completely honest with them about what happened, allowed them to believe things that were not true, or intentionally misled them'' (24%), and a desire to ''deter subsequent malpractice by the physician and/or to seek revenge'' (19%) [18]. Other studies have similarly found failure to provide explanations and poor communication generally are associated with litigation [1,19,21,34,35,48].…”
Section: Apologies and Patientsmentioning
confidence: 99%
“…The trust in patient-physician relationship is compromised [15][16][17], and it has a "corrosive effect on morale" [5]. Not surprisingly, associations have been found between the number of patient complaints filed regarding a doctor and the likelihood of malpractice litigation against said clinician [18]. In the most extreme cases, news agencies pick up stories of inappropriate behaviors, severely tarnishing the reputation of a hospital.…”
Section: The Ripple Effect Of Disruptive Behaviormentioning
confidence: 99%
“…Minor deviations from appropriate behavior must be recognized and intervened upon to prevent escalation [18,42]. Anonymity of reporting parties must be assured to reduce the fear of retaliation [43].…”
Section: Vignettes In Patient Safety -Volumementioning
confidence: 99%
“…Thus, physicians need to focus on patients' satisfaction with care because it may drive patient volume more than technical acumen alone. Another reason physicians might focus on patients' experience of care is that there is evidence suggesting that "the frequency with which physicians are sued is related in part to patients' satisfaction with interpersonal aspects of medical care" [10,11]. While these may not be the primary reasons for physicians to focus on patients' experience of care, doing so may actually provide operational benefit, in addition to better patient care.…”
Section: Benefits Of Patient Experience Measurementmentioning
confidence: 99%